2022
DOI: 10.1007/s10457-022-00783-2
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of open pasture to hardwood silvopasture enhanced soil health of an ultisol

Abstract: glomalin-related soil protein, soil enzymatic activities, and microbial community structure. The soil OM content in HSP (64 g kg −1 ) was greater (p < 0.05) than BSP and OP (55 g kg −1 ). The BSP soils had about 45% and 52% more (p < 0.05) microbial biomass carbon and nitrogen than OP soils. The HSP soils had 60% greater (p < 0.05) microbial biomass nitrogen than OP soils. The BSP supported greater (p < 0.05) β-glucosidase and urease activities than the HSP and OP treatments, while greater (p < 0.05) β-glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The increased SOC content and lower BD in the silvopasture at the 0–15 cm depth led to higher SOC and BD SMAF scores and, consequently, greater soil quality than the conventional pasture system (Table 2 ). The milder microclimate created by the trees and the greater soil moisture may have altered microbial community and activity, thus slowing SOM decomposition compared to the pasture only system 21 . Increased SOM levels are generally linked with enhanced nutrient availability and soil fertility, improved soil structure, and greater water retention, microbial activity and diversity, ultimately leading to greater system productivity 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased SOC content and lower BD in the silvopasture at the 0–15 cm depth led to higher SOC and BD SMAF scores and, consequently, greater soil quality than the conventional pasture system (Table 2 ). The milder microclimate created by the trees and the greater soil moisture may have altered microbial community and activity, thus slowing SOM decomposition compared to the pasture only system 21 . Increased SOM levels are generally linked with enhanced nutrient availability and soil fertility, improved soil structure, and greater water retention, microbial activity and diversity, ultimately leading to greater system productivity 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies support our results on greater soil quality in silvopasture systems and demonstrate the positive impacts of agroforestry practices on SOC, nutrient availability, and soil biodiversity 46 . Poudel et al (2022) 21 showed that a 25-year old temperate hardwood silvopasture in the Southern Appalachian Ridge and Valley region, VA, had higher SOM, microbial biomass C, and enzyme activity than pasture without trees. Moreover, the authors showed that increases varied according to tree species, stand age, and system management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this decade, we observed annual growth, with a peak number of publications in the year 2022 with 708 articles, suggesting that silvopastoral systems are a topic of great interest at a global level. The conversion of extensive pastures to silvopasture with timber trees as a measure to improve soil health [49] and the restoration of degraded lands [50] were addressed. Other studies focused on the combination of silvopastoral systems and remaining forests under livestock strategies [51], the benefits of thermal cooling in tropical silvopastoral systems [52], and how these can enhance the mitigation of climate change effects related to greenhouse gas emissions generated by cattle ranching activities [53].…”
Section: Period IV (2014-2022)-landscape Restorationmentioning
confidence: 99%
“…Finally, most of the reported research was carried out in developed countries and in countries that have presented significant increases in activities focused on silvopasture [51,52,58,59]. Regarding the Americas, in the United States, open grassland conservation benefits silvopastoralism by improving soil health [49]. Likewise, researchers reported that silvopastoral systems can contribute to −0.32 • C to −2.4 • C of cooling for every 10 metric tons of woody carbon per hectare [52].…”
Section: Country Classification By Publicationsmentioning
confidence: 99%